2000
DOI: 10.1128/aac.44.4.885-890.2000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of Imipenem, Meropenem, Cefepime, and Ceftazidime in Rats with Experimental Pneumonia Due to a Carbapenem-Hydrolyzing β-Lactamase-Producing Strain of Enterobacter cloacae

Abstract: The antibacterial activities of imipenem-cilastatin, meropenem-cilastatin, cefepime and ceftazidime against Enterobacter cloacae NOR-1, which produces the carbapenem-hydrolyzing ␤-lactamase NmcA and a cephalosporinase, and against one of its in vitro-obtained ceftazidime-resistant mutant were compared by using an experimental model of pneumonia with immunocompetent rats. The MICs of the ␤-lactams with an inoculum of 5 log 10 CFU/ml were as follows for E. cloacae NOR-1 and its ceftazidime-resistant mutant, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…A limitation of the present study was the evaluation of only one strain, as differences among strains can affect study results despite similar MICs (26). We also did not perform a PK evaluation of the antibiotics in rats, which might contribute to the interpretation of our findings (15,(17)(18)(19), but previous in vitro studies have demonstrated that combinations of TIG and MER and TIG and PMB present favorable PK results (27,28).…”
Section: Fig 2 Survival Curves Of a Rat Model Of Sepsis Infected Withmentioning
confidence: 52%
“…A limitation of the present study was the evaluation of only one strain, as differences among strains can affect study results despite similar MICs (26). We also did not perform a PK evaluation of the antibiotics in rats, which might contribute to the interpretation of our findings (15,(17)(18)(19), but previous in vitro studies have demonstrated that combinations of TIG and MER and TIG and PMB present favorable PK results (27,28).…”
Section: Fig 2 Survival Curves Of a Rat Model Of Sepsis Infected Withmentioning
confidence: 52%
“…These rats were rendered neutropenic by the intraperitoneal administration of cyclophosphamide and renally insufficient by subcutaneous uranyl nitrate administration (13). The pharmacokinetic parameters of the antibiotics were similar to those observed when a 1-g imipenem dose, a 2-g cefepime or ceftazidime dose, a 4.5-g piperacillin-tazobactam dose, or 1-to 2-g aztreonam doses are given intravenously to healthy humans ( Table 1).…”
mentioning
confidence: 70%
“…At that time, rats were randomly assigned to a control group (no antibiotic) and six treatment groups. Treatment groups received intraperitoneal injections of either imipenemcilastatin (30 mg/kg of body weight/8 h), cefepime (60 mg/kg/8 h), ceftazidime (60 mg/kg/8 h), piperacillin-tazobactam (120 and 15 mg/kg/6 h, respectively), or aztreonam (30 or 60 mg/ kg/6 h) (1,2,12,13). These dosages were retained to mimic plasma concentrations observed with highest recommended doses of these ␤-lactams in humans.…”
mentioning
confidence: 99%
See 2 more Smart Citations